PENGEMBANGAN SISTEMKEAMANAN PANGAN TERPADU DALAM MEWUJUDKAN EFEKTIVITAS IMPLEMENTASI IZIN EDAR PRODUK PANGAN INDUSTRI RUMAH TANGGA (PIRT) - Hermanu, Bambang (Proceeding SENDI_U, 2015)
Health law definitely states that food and beverages can only be distributed in public upon issuance of adistribution permit. Hence, prior to being permitted the food and beverages are not allowed to bedistributed in public. On the other hand, in line with the development of society, the rapid distribution ofprocessed food (food and beverages), especially those produced as home industries, with or withoutpackaging, has caused much concerns due to violation of the distribution permit and contamination of theproducts with its associated health risks in the short, medium, and long term. The present researchproposed three basic questions. Firstly, how did the implementation of a distribution permit of food andbeverages promote food safety in Semarang. Secondly, what factors if any, discourage the implementationof a distribution permit of food and beverages to promote the food safety. Normative and empirical legalresearch method has been employed for this research, using both primary and secondary data. Theprimary data were collected in the field; whereas the secondary data came from primary, secondary, andtertiary legal establishments, respectively. Results of this study showed that implementation of adistribution permit of food and beverages produced by home industries are in general the responsibilityof the Office of Health in the City or Regency, with the issuance of Induction Certificates and HomeIndustry Products Certificates. These certificates are officially legal permits as a guarantee that the foodand beverages produced by home industries are safe; and as a protection against food additives thatcould be detrimental to health. The implementation is basically a persuasive action under the assumptionof human dignity rather than tough and normative legal procedures. Obstacles to the implementationincluded factors such as economic condition, inadequate knowledge of both consumers and producers,as well as the weak legal measures on food safety. A number of factors were found to affect the foodsafety in Indonesia, i.e. food system, culture, food chain, environment, nutrition and epidemiology. It wassuggested that education for consumers to raise awareness of food safety was of prime importance.Consumers should be made aware and fully understand the food safety system and its associated healthrisks due to insecure food safety.Keywords : distribution permit of food and beverages, food safety, food system.